Changes of strength and maximum power of lower extremities in adolescent handball players during a two-year training cycleo - Górski, M.; Starczewski, M.; Pastuszak, A.; Mazur-Rózycka, J.; Gajewski, J.; Busko, K. (Journal of Human Kinetics, 2018)
The aim of the study was to investigate changes of strength and power of the lower extremities in adolescent handball players during a two-year training cycle. Thirty-one male handball players (age 16.0 ± 0.2 years, body mass 81.4 ± 9.7 kg, body height 188.2 ± 6.4 cm) took part in this study. All tests were conducted three times at the beginning of a one-year training programme. The maximum joint torque (JT) of flexors and extensors of the elbow, shoulder, hip, knee and trunk was measured under static conditions. Power of lower extremities was assessed with a repeated sprint ability (RSA) test on a cycloergometer and jump tests: akimbo counter-movement jump (ACMJ), counter-movement jump (CMJ) and spike jump tests on a force plate. Peak power (PP) increased from 914.8 ± 93.9 to 970.0 ± 89.2 and 1037.8 ± 114.4 W (p < 0.05) following the RSA test results. Maximum power increased significantly (p < 0.05) in ACMJ (1951.9 ± 359.7 to 2141.9 ± 378.5 and 2268.5 ± 395.9 W) and CMJ tests (2646.3 ± 415.6 to 2831.2 ± 510.8 and 3064.6 ± 444.5 W). Although significant differences in JT (p < 0.05) were observed during the two year period, their values related to body mass for the lower right extremity, sum of the trunk and sum of all muscle groups increased significantly between the first and the second measurement (from 13.7 ± 1.8 to 14.58 ± 1.99 N·m·kg-1, from 9.3 ± 1.5 to 10.39 ± 2.16 N·m·kg-1, from 43.4 ± 5.2 to 46.31 ± 6.83 N·m·kg-1, respectively). The main finding of the study is that PP in the RSA test and maximal power in the ACMJ and CMJ increase in relation to training experience and age in the group of youth handball players.